2016
DOI: 10.1007/s00705-016-2966-9
|View full text |Cite
|
Sign up to set email alerts
|

A naturally truncated NS1 protein of influenza A virus impairs its interferon-antagonizing activity and thereby confers attenuation in vitro

Abstract: The non-structural protein of influenza A virus (NS1A protein) is a multifunctional protein that antagonizes host antiviral responses and contributes to efficient viral replication during infection. However, most of its functions have been elucidated by generating recombinant viruses expressing mutated NS1 proteins that do not exist in nature. Recently, the novel H3N8 A/Equine/Kyonggi/SA1/2011 (KG11) influenza virus was isolated in Korea from horses showing respiratory disease symptoms. KG11 virus contains a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Our previous study shows that IFN-g can also be released from mouse mast cells during IAV infection and regulate a series of pulmonary epithelial cell apoptosis (6). To date, various reports have shown that DPs can stimulate the immune response via high-level expression of type I IFN (39,40). However, few reports have assessed the action of type II IFN in the immune response induced by DPs.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study shows that IFN-g can also be released from mouse mast cells during IAV infection and regulate a series of pulmonary epithelial cell apoptosis (6). To date, various reports have shown that DPs can stimulate the immune response via high-level expression of type I IFN (39,40). However, few reports have assessed the action of type II IFN in the immune response induced by DPs.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza viruses containing a truncated NS1 failed to activate the PI3K/Akt pathway, grew slower and formed small plaques in tissue culture [429]. The truncated NS1 protein also conferred an attenuated phenotype due to its inability to inhibit host antiviral responses [430].…”
Section: P13k-p110a Signalling Pathwaymentioning
confidence: 99%
“…The main genetic changes observed were in the HA gene without any antigenic drift. Recently, H3N8 A/Equine/Kyonggi/SA1/2011 (KG11) was isolated in Korea which had naturally truncated NS1 protein coding gene (Lee et al, 2017 ). Recently, genome of two equine influenza strains namely A/equine/Kostanay/9/2012(H3N8) and A/equine/LKZ/9/2012(H3N8) isolated from Kazakhstan was sequenced completely.…”
Section: Epidemiology and Evolutionmentioning
confidence: 99%